2003
DOI: 10.1016/s1099-5129(03)00047-3
|View full text |Cite
|
Sign up to set email alerts
|

Management of syncope referred urgently to general hospitals with and without syncope units

Abstract: Although only a minority of patients admitted as an emergency are referred to the syncope unit, overall management is substantially affected. It is speculated that the use of a standardized approach, such as that typically adopted in the syncope unit, is able to influence overall practice in the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
2
3

Year Published

2007
2007
2010
2010

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 9 publications
5
59
2
3
Order By: Relevance
“…In the Czech Republic, there are not enough fi nancial resources to establish and maintain SMUs which have been shown to be highly eff ective in initial syncope evaluation. In this study, we confi rmed the original results 3,6,10 that simple anamnestic data and ECG records organized in the form of a point score can help to recognize cardiac syncopes, which are considered to be the most dangerous 10 . From the three evaluated scores (EGSYS-U, EGSYS-M, and OESIL), we recommend that EGSYS-U be used in ED syncope management, because (at the appropriate cut-off level) it appears to have both high sensitivity and high specifi city.…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…In the Czech Republic, there are not enough fi nancial resources to establish and maintain SMUs which have been shown to be highly eff ective in initial syncope evaluation. In this study, we confi rmed the original results 3,6,10 that simple anamnestic data and ECG records organized in the form of a point score can help to recognize cardiac syncopes, which are considered to be the most dangerous 10 . From the three evaluated scores (EGSYS-U, EGSYS-M, and OESIL), we recommend that EGSYS-U be used in ED syncope management, because (at the appropriate cut-off level) it appears to have both high sensitivity and high specifi city.…”
Section: Resultsmentioning
confidence: 59%
“…The extension of syncope as a public health problem has been documented since the Framingham Study Report 2 showed the incidence of self-reported syncope to be 6.2 per 1000 person-years with a cumulative incidence of approximately 6% over 10 years. It has been reported [2][3][4][5][6] that syncope accounts for about 5% of Emergency Department (ED) visits and in the age group of patients older than 65, syncope becomes the sixth most common cause of hospitalization. Shen et al 5 report that in selected patient populations, the lifetime prevalence of syncope reaches almost 50%.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations